2016
DOI: 10.1186/s12933-016-0350-4
|View full text |Cite
|
Sign up to set email alerts
|

Risks of cardiovascular diseases associated with dipeptidyl peptidase-4 inhibitors and other antidiabetic drugs in patients with type 2 diabetes: a nation-wide longitudinal study

Abstract: BackgroundSeveral antidiabetic drugs (i.e., sulfonylureas; SU, rosiglitazone) have been reported to be associated with increased risks of cardiovascular diseases (CVD) in patients with type 2 diabetes mellitus (T2DM). Dipeptidyl peptidase-4 inhibitors (DPP4i) are newly available antidiabetic drugs. Most studies only compared DPP4i with a placebo or SU, or targeted a specific CVD event of interest (i.e., heart failure; HF). Comparative research of CVD risks of DPP4i with other antidiabetic drugs (i.e., metformi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 50 publications
1
56
1
1
Order By: Relevance
“…With regard to cardiovascular risk associated with DPP‐4Is relative to α‐GIs in Asian patients, Ou et al reported that there were no major differences in the risk of MI, HF, and stroke between DPP‐4Is and α‐GIs. In general, our results support these findings and contribute to providing more robust evidence on the widespread use of α‐GIs in Asia due to its pharmacological action and lower cardiovascular risk .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to cardiovascular risk associated with DPP‐4Is relative to α‐GIs in Asian patients, Ou et al reported that there were no major differences in the risk of MI, HF, and stroke between DPP‐4Is and α‐GIs. In general, our results support these findings and contribute to providing more robust evidence on the widespread use of α‐GIs in Asia due to its pharmacological action and lower cardiovascular risk .…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the results of sensitivity analysis, in which clinical outcome with mortality was used as a definition of censoring, were consistent with primary analysis. The risk of HF was also examined by comparison with results from previous studies . Lastly, we only focused on DPP‐4Is as monotherapy and could not investigate the effect of individual DPP‐4Is or combination therapy with other drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies revealed that both DPP-4i and metformin users had a significantly lower risk for composite cardiovascular diseases [18]. The combination therapy of DPP4i with conventional OHA led to an improvement in passive left ventricular compliance [20].…”
Section: Discussionmentioning
confidence: 99%
“…60,61 In randomized trial of 5380 patients with T2DM and recent acute coronary syndrome in the last 15-90 days, alogliptin was non inferior to placebo with regards to the combined primary outcome of cardiovascular death, nonfatal MI or non-fatal stroke after a median follow up of 18 months. 62 A post hoc analysis showed that alogliptin had no effect on heart failure outcomes, including a composite of cardiovascular death and heart failure hospitalization. 63 In the trial to evaluate cardiovascular outcome after treatment with sitagliptin (TECOS) study, which randomized 14,671 patients with T2DM, sitagliptin was non-inferior to placebo for the primary composite outcome of cardiovascular death, non-fatal MI, non-fatal stroke or hospitalization for unstable angina with no difference in hospitalization rates for heart failure.…”
Section: Dipeptidyl Peptidase-4 Inhibitors (Dpp-4 Inhibitors)mentioning
confidence: 99%